Advances in therapeutic strategies for Leber's hereditary optic neuropathy. (2nd December 2015) - Karanjia, Rustum; Sadun, Alfredo A.
Abstract : Introduction : Leber's hereditary optic neuropathy (LHON) is a rare mitochondrial disease which preferentially affects the optic nerve. A genetic defect in the mitochondrial DNA encoding complex I of the respiratory chain underlies this genetic disorder. Patients typically present with subacute vision loss in one eye followed by the loss of vision in the second eye approximately 6 weeks later, ultimately leading to blindness. Areas covered : In this review, we discuss failed and active therapies as well as the future of clinical trials in LHON. A review of the literature was performed and articles were identified using PubMed. The search terms LHON and treatment were used. These publications were paired to the clinical trials listed on the clinicaltrials.gov website. Expert opinion : Several therapies have been tested to treat LHON; however, so far, no double-blind placebo-controlled clinical trial has been successful in the treatment of LHON. Avoidance of triggers which generate reactive oxygen species and treatment with idebenone is the best currently available therapy for LHON.